Pneumococcal conjugate serotype distribution and predominating role of serotype 3 in German adults with community-acquired pneumonia - Forstner, Christina; Kolditz, Martin; Kesselmeier, Miriam; Ewig, Santiago; Rohde, Gernot; Barten-Neiner, Grit; Rupp, Jan; Witzenrath, Martin; Welte, Tobias; Pletz, Mathias W. (Vaccine, 2020)
•PCV13 serotypes were present in 7.4% of German adults with pneumonia.•Serotype 3 was the most common serotype detected by SSUAD.•Serotype 3 can cause severe pneumonia.•Serotype 3 was frequently missed by conventional microbiology.•Changes in overall PCV coverage were not detected during years 2013 to 2016 in Germany. Implementation of the 7-valent pneumococcal conjugate vaccine (PCV7) in infant vaccination programs has substantially reduced the burden of PCV7 serotypes also in adult community-acquired pneumonia (CAP). Currently, it is unclear, if this extensive herd protection effect can be extrapolated to the additional 6 serotypes included in the 13-valent pneumococcal conjugate vaccine (PCV13), which replaced PCV7 in Germany in 2010. We investigated changing trends for PCV13 serotypes in adult CAP patients between three to seven years after implementation of PCV13 infant immunization in Germany. Between December 2012 and January 2017, urine samples from German adult patients with radiologically confirmed CAP were prospectively collected by the multi-center cohort study CAPNETZ and analyzed by the serotype-specific multiplex urinary antigen detection assay (SSUAD) allowing for the detection of PCV13 serotypes. PCV13 serotypes were found in 59 of 796 (7.4%) patients with all-cause CAP, most prevalent was serotype 3 (30 of 59 patients, 50.8%). All patients with serotype 3-CAP were admitted to hospital and the majority required oxygen at admission (83.3% of patients with serotype 3-CAP versus 50.9% of patients with pneumococcal CAP by other serotypes, p = 0.005). Compared to SSUAD testing, conventional microbiological workup missed 27 of 30 (90.0%) serotype 3-CAP cases. We could not observe a time trend in the proportions of PCV13 serotypes and serotype 3 in all-cause CAP between 2013 and 2016 (OR trend per year 0.84, 95% CI 0.64–1.11 for PCV13 serotypes and OR trend per year 0.95, 95% CI 0.70–1.28 for serotype 3). Conclusions: Conventional methods underestimate serotype 3-CAP that can cause severe disease. Changes in overall PCV13 coverage were not detected during the years 2013 to 2016, mostly driven by a high proportion of serotype 3.